2010
DOI: 10.1007/s10562-010-0447-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of Benzyl Alcohol over Activated Carbon Supported Manganese and Vanadium Catalysts: Effect of Surface Oxygen-Containing Groups

Abstract: In this contribution, the selective oxidation of benzyl alcohol using molecular oxygen over supported manganese and vanadium catalysts was investigated. The catalytic activities were significantly improved after preoxidizing the activated carbon support materials. Characterizations of nitrogen physisorption, X-ray diffraction, transmission electron microscopy, and X-ray absorption were involved to examine the physicochemical properties of as-prepared catalysts. By ruling out the effects of specific surface are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…64% of conversion was reached when MnO x /AC (5 wt%) was used as a catalyst. 212 It was found that highly dispersed vanadium species with a distorted tetrahedral coordination were active for oxidation of substituted phenyl alcohols (TOF up to 22 h À1 , based on the molar content of V 2 O 5 ). 204 In addition, selectivity to carbonyl compounds was always more than 99% for all tested phenyl alcohols.…”
Section: Catalysts Design For Aerobic Selective Oxidation Of Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…64% of conversion was reached when MnO x /AC (5 wt%) was used as a catalyst. 212 It was found that highly dispersed vanadium species with a distorted tetrahedral coordination were active for oxidation of substituted phenyl alcohols (TOF up to 22 h À1 , based on the molar content of V 2 O 5 ). 204 In addition, selectivity to carbonyl compounds was always more than 99% for all tested phenyl alcohols.…”
Section: Catalysts Design For Aerobic Selective Oxidation Of Alcoholsmentioning
confidence: 99%
“…205 Among various characterization techniques, X-ray absorption spectroscopy (XAS) with synchrotron light source has emerged as a powerful technique to probe the active site in catalysts. 203,204,212,213 X-Ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) provide information about the local coordination and electronic properties of the catalytic active centers. For example, based on the Mn K-edge XANES spectra of manganese oxide standards with different oxidation states (MnO, Mn 3 O 4 , Mn 2 O 3 , MnO 2 and MnOOH), a linear relation was found to give a good match to the set of five experimental edge positions versus oxidation states (as shown in Fig.…”
Section: Catalysts Design For Aerobic Selective Oxidation Of Alcoholsmentioning
confidence: 99%
“…Vanadium plays important roles in many fields, such as ferrous and nonferrous alloy production [1], thermistors [2], and catalysts [3]. More than 87% of the vanadium resources exist in the form of stone coal in China [4].…”
Section: Introductionmentioning
confidence: 99%
“…BET surface area of AC (1195 m 2 /g) was investigated by N 2 adsorption/desorption, −196 ∘ C, with particle size ranging from 75 to 106 m. Chen et al have reported that the surface area does not play a major role in catalysis through activated carbon. Although the oxygen containing surface functional group plays a crucial role in catalysis [25]. Figure 3 shows the XRD pattern of AC.…”
Section: Characterization Of the Catalystmentioning
confidence: 99%